Offera: A method for evaluating office risk factors of work-related musculoskeletal disorders (WMSDs). - Abdol Rahman, Mohd Nasrull; Mohamad, Siti Shafika (Work, 2026)
Background: Office risk factors linked to work-related musculoskeletal disorders (WMSDs) are frequently evaluated using ergonomic risk assessment tools. Objective: This study aimed to explore the office risk factors linked to work-related musculoskeletal disorders (WMSDs) by developing an Office Ergonomic Risk Assessment (OFFERA) method. Methods: The development and evaluation of OFFERA method, divided into two stages which include the development of OFFERA system components and psychometric properties of OFFERA method. Results: In the reliability testings, observers showed strong agreement both between different observers (K = 0.62–0.78) and when the same observer repeated their measurements (K = 0.81–0.96). In the validity testings, the relationship between the final score of OFFERA and the musculoskeletal symptoms is statistically significant for the wrists/hands, lower back, knees, and ankle/leg. Conclusion: Tests have demonstrated that the OFFERA approach can be easily used across many different types of office work.